A theoretical study of the phenomenon of social alienation among university youth In the United Arab Emirates - Albdwawi, Amna; Nashwan , Ayat (Al-Adab Journal, 2024)
The research explores the concept of social alienation, a phenomenon that leads to social powerlessness, meaninglessness, normlessness, and isolation. It examines the role of religious, psychological, and social contexts in understanding social alienation. The study identifies a social shift in Emirati society affecting youth, highlighting the visibility of social alienation aspects among them.The research focuses on various social alienation theories, including Marx's explanation of social alienation, Durkheim's association of suicide with the breakdown of social bonds, and Max Weber's analysis of bureaucracy's impact on individual freedom and creativity. Melvin Seeman's comprehensive analysis of social alienation highlights five essential aspects. The study emphasizes the need to study social alienation in various contexts and develop support and intervention strategies to address challenges in social and educational environments. It also emphasizes the importance of understanding the interactions between social alienation and emerging challenges at the societal level.The research recommends enhancing social communication, supporting social integration, and improving working conditions, with a focus on psychological support and encouragement of continuous learning. It also emphasizes the importance of Emirati cultural identity and community partnerships in building a supportive environment for social adaptation and individual well-being.The research contributes valuable insights to understanding and addressing social alienation among youth, contributing to a more comprehensive understanding of the topic.